Life on a leaf: the epiphyte to pathogen continuum and interplay in the phyllosphere - Thomas, G; Kay, WT; Fones, HN (BioMed Central, 2024)
Epiphytic microbes are those that live for some or all of their life cycle on the surface of plant leaves. Leaf surfaces are a topologically complex, physicochemically heterogeneous habitat that is home to extensive, mixed communities of resident and transient inhabitants from all three domains of life. In this review, we discuss the origins of leaf surface microbes and how different biotic and abiotic factors shape their communities. We discuss the leaf surface as a habitat and microbial adaptations which allow some species to thrive there, with particular emphasis on microbes that occupy the continuum between epiphytic specialists and phytopathogens, groups which have considerable overlap in terms of adapting to the leaf surface and between which a single virulence determinant can move a microbial strain. Finally, we discuss the recent findings that the wheat pathogenic fungus Zymoseptoria tritici spends a considerable amount of time on the leaf surface, and ask what insights other epiphytic organisms might provide into this pathogen, as well as how Z. tritici might serve as a model system for investigating plant–microbe-microbe interactions on the leaf surface.